Primary giant hepatic neuroendocrine neoplasms in a young adult: case report and literature review - Luo, Xue; Bie, Xingxing; Luo, Na; Huang, Wenting (Frontiers in Oncology, 2025)
Primary hepatic neuroendocrine neoplasms (PHNENs) are a rare type of neuroendocrine tumors originating in the liver. These tumors are characterized by non-specific clinical symptoms and atypical imaging features, making differentiation from other primary hepatic masses, such as hepatocellular carcinoma (HCC) and parasitic lesions, challenging. The diagnosis of PHNENs is based on characteristic histological features associated with this condition and results from immunohistochemistry assays. Here, we report on a case of a 22-year-old female presenting with a large hepatic neoplastic lesion. Computed tomography (CT) imaging results revealed a highly vascularized mass with clear boundaries located in the right lobe of the liver, suggesting a diagnosis of HCC. The patient underwent a fine-needle aspiration biopsy and subsequent complete surgical resection of the tumor. Results from both the fine-needle aspiration and histology of the surgically resected specimen showed that the tumor cells were arranged in a solid structure with a trabecular pattern. The tumor cells exhibited positive expressions for the epithelial cell markers AE1/AE3, along with the neuroendocrine markers, synaptophysin (Syn), chromogranin (CgA), and CD56 as based on results from immunohistochemical staining. The Ki-67 proliferation index was > 20%, and the mitotic count was > 20 per 2 square millimeters, leading to a final diagnosis of a hepatic neuroendocrine neoplasms, Grade 3 (G3). PHNENs are extremely rare, and, to our knowledge, there have been no reports in the literature of adolescents or young adults diagnosed with the G3-type.